Toward improving the specificity of perturbation-based training through assessment of dynamic balancing responses: a series of N-of-1 studies in subacute stroke. Issue 3 (September 2021) - Zadravec, Matjaž; Olenšek, Andrej; Rudolf, Marko; Bizovičar, Nataša; Goljar, Nika; Matjačić, Zlatko
Abstract : Perturbation-based balance training (PBT) has been shown to improve reactive balancing abilities in chronic stroke. To inform future investigations in the subacute phase of stroke, the objective of this series of N-of-1 studies was to investigate the range of balancing responses to unexpected mechanical perturbations applied to the pelvis during walking on an instrumented treadmill before and after PBT training. Three subacute stroke subjects were assessed on each occasion with clinical tests and biomechanical measurements following perturbations applied in forward, backward, inward and outward directions. After 15 daily sessions of PBT, most clinical mobility outcomes showed improvements in all three subjects. Assessment of reactive balancing also showed improvements in all subjects when responding to perturbations in backward and inward directions whereas the changes following perturbations in forward and outward directions were subject-specific. The results suggest that PBT should be individually tailored to target balance deficiencies identified through a serial biomechanical assessment.